Radiology Department Workers' Knowledge Regarding COVID-19: A Cross-Sectional Study: Pengetahuan Pekerja Departemen Radiologi Mengenai COVID-19: Sebuah Studi Cross-Sectional - Abdul-Ra'aoof, Husham Hussain; Mizher, Wedad Amer; Tiryag, Ali Malik; Hanoun, Amina Abdul-Rhman; Hafed, Mohamed Hassan (Indonesian Journal on Health Science and Medicine, 2025)
Background: Because radiology department employees are thought to be more susceptible to infection, they must understand infection control procedures and receive the necessary training to wear personal protective equipment. Objectives: The purpose of this study is to evaluate radiology department employees' knowledge of COVID-19 and determine how that knowledge relates to the employees' sociodemographic information. Methods: Between February 25 and March 16, 2021, 85 employees of hospitals in the Thi-Qar governorate's radiology departments participated in a descriptive cross-sectional study. To gather the information needed to meet the study's objectives, a unique questionnaire was created. The data was statistically analyzed using the Social Science Statistics software version 23, and the findings were presented as percentages and frequencies. The correlation between the various variables was evaluated using the mean score and significance. Results: Fifty-four (63.9%) and 31 (36.5%) of the 85 participants were men and women, respectively; 28 (32.9%) were in the 20–30 age range; 61 (71.8%) were married; 45 (52.9%) had a diploma; 46 (54.1%) were employed at X-ray units; approximately half (42, 49.4%) were radiographers; and 43 (50.6%) had been employed in the radiology department for 1–10 years. Conclusion: In summary, 78 (91.7%) and 7 (8.4%) individuals, respectively, had high and medium levels of overall knowledge regarding COVID-19 among radiology department employees; no discernible correlation was found between the study population's features and overall expertise.Highlight : Most radiology department workers demonstrated high knowledge about COVID-19. No significant link was found between knowledge levels and sociodemographic factors. Strongest knowledge was in infection prevention and clinical characteristics. Keywords : COVID-19, Radiology Department, Knowledge, Infection Prevention, Cross-Sectional Study